Effect of Online Bus Booking on Customer Satisfaction: A Study of ABC Transport, Utako Terminals, Abuja, Nigeria. - Nduji Romanus; Marcus Garvey Orji; Oriaku Chris (Britain International for Academic Research (BIAR) Publisher, 2024)
In the Nigerian business environment, one of the most unresolved problems in transportation industries is the poor inclusion of online bus booking in the scheme of things. These failures revolve round the fit between managers and staff of the organization to work in agreement to welcome the new arrival. This study focused on the effect of online bus booking (e-ticketing) on customer satisfaction, with emphasis on ABC transport, Utako terminals, Abuja, Nigeria. The specific objective was: to ascertain the effect of e-mail ticketing system on customer satisfaction of ABC transport, Abuja terminals, investigate the effect of web-based ticketing system on customer satisfaction of ABC transport, Utako terminals, and to find out the relationship between e-bus booking or e-ticketing and customers satisfaction of ABC transport, Utako terminals, Abuja. The study adopted the survey research design. Stratified random sampling was applied and the population of the study was 475 while sample sized of 217 was determined using taro yamani formula. Data was analyzed by regression method and findings revealed that online bus booking (e-ticketing) has effect on customer satisfaction of ABC transport, Utako terminals, Abuja, Nigeria. The study concluded that with the arrival of online bus booking system, service quality which is a significant factor which determines passengers' satisfaction will have a positive change. Hence, if passengers are satisfied with the service offered their level of patronage and loyalty to the brand will significantly increase. The study recommended that Transport companies in Nigeria should encourage the use of digital ticketing systems among passengers through incentives such as discounts so as to improve passenger usage.